Overview Of Anemia In Young Women Low Body Mass Index (Thin Category): Gambaran Anemia Pada Remaja Putri Dengan Indeks Massa Tubuh Rendah (Kategori Kurus) - Risna’im, Annisa Rohmania; Mahtuti, Erni Yohani; Masyhur, Muhammad; Faisal (Medicra (Journal of Medical Laboratory Science/Technology), 2022)
In the period of growth and development, adolescents need more nutrients. Adolescents face many health problems due to biological and psychological changes as well as malnutrition. Anemia is a common health problem. Riskesdas data in 2018, in Indonesia there is a prevalence of anemia of 48.9%. Cases of anemia often occur in the age group of 15-24 years and 25-34 years. This study aims to determine the state of anemia with a lean body mass index in adolescent girls at SMK Madani Turen, Malang Regency. The research design used is descriptive quantitative with a cross sectional approach and a total of 101 respondents. The samples obtained had a lean body mass index of 24 people (23.76%) and the majority were known not to be anemic, namely 17 people (70.83%) and those who had anemia were 7 people (29.16%). The p value of the Fisher's exact test is 0.000 if the p value is <0.05, which means Ho is rejected, it can be concluded that there is a relationship between body mass index and Hb levels in female students at SMK Madani Turen.